Optimization of reaction parameters in the conversion of PET to produce BHET - Capeletti, Maria Rosa (2017)
The conversion of poly(ethylene terephthalate) (PET) was analyzed in order to define the optimal conditions for the Bis(2-Hydroxyethyl) terephthalate (BHET) yield as regards catalyst use (zinc acetate), glycol (ethylene glycol), reaction time and temperature. These conditions were optimized so as to decrease the consumption of catalyst and glycolytic agents aiming to extend the analysis to achieve continuous recycling at a greater scale. At the same time, an analysis of the activity of different catalysts (zeolites, acid, and basic resins) was performed; no BHET yields of commercial interest were obtained. The results indicate that a very small catalyst/PET mass ratio and a low glycol/PET ratio are necessary. The reactions were carried out at a temperature of 1958C and a reaction time of 1 h: under these conditions, BHET yield is 30% (starting from pure PET) and up to 88.2% (recycling oligomers plus pure PET).